Chip-based genotyping by mass spectrometry - Tang, Kai (The National Academy of Sciences, 1999)
Silicon chips with immobilized target DNAs were used for accurate genotyping by mass spectrometry. Genomic DNAs were amplified with PCR, and the amplified products were covalently attached to chip wells via N-succinimidyl (4-iodoacetyl)aminobenzoate (SIAB) chemistry. Primer annealing, extension, and termination were performed on a 1-μl scale directly in the chip wells in parallel. Diagnostic products thus generated were detected in situ by using matrix-assisted laser desorption ionization mass spectrometry. This miniaturized method has the potential for accurate, high-throughput, low-cost identification of genetic variations.